Explaining State Preemption of Local Laws: Political, Institutional, and Demographic Factors. Issue 2 (25th September 2019) - Flavin, Patrick; Shufeldt, Gregory
Abstract: Despite increasing popular and media attention to the preemption of local policymaking by state governments, the empirical political science literature on preemption remains relatively scarce. After first identifying and discussing state preemption laws across twenty-one diverse public policies, we investigate how political, institutional, and demographic factors predict the implementation of these laws. Our empirical analysis reveals that states where Republicans control both legislative chambers and the governorship, with more politically conservative citizens, a higher percentage of African Americans, and a stronger conservative interest group presence passes more laws that preempt local policymaking. Our results demonstrate that state preemption efforts are more closely associated with political and demographic factors and less associated with institutional forces.